The Factoring Market in Poland and the European Union - Włodarczyk, Bogdan; Ostrowska, Aleksandra (Olsztyn Economic Journal, 2017)
The service of factoring, thanks to the constant financing of receivables, prevents the creation of payment backlogs enabling the regulation of liabilities on time and, as a result, improves the financial liquidity of economic entities. It is thanks to the reasons mentioned above that the use of the service of factoring is bigger in Poland than in other countries of the EU. The aim of this article is an analysis of the factoring services in Poland with regards to the EU. Taking into consideration the meaning of factoring for the enterprise sector and the banking sector which finances it, an analysis and evaluation of the Polish factoring services market was made on the bases of factoring service profiles provided by clients and entities.Together with the dynamics of the development of companies and the range of the factoring services provided, the number of business entities choosing this service as an alternative to a revolving loan is growing. In the Polish market, the increase is not correlated with the size of a given region’s economy, but the number of enterprise entities.